CHARACTERIZATION OF ENOLA HOLMES IN THE CASE OF THE MISSING MARQUESS: A STUDY OF LIBERAL FEMINISM - Halimatus Sakinah; Ari Setyorini; Masulah Masulah (PHILOLOGY Journal of English Language and Literature, 2022)
This study attempts to portray a female character, Enola Holmes, in Nancy Springer’s novel series entitled The Case of the Missing Marquess (2006). This research focuses on examining these research problems: 1) how is Enola Holmes characterized differently from most teenage girls at the setting of time, and 2) what spirit of feminism is illustrated by the novel through the character of Enola Holmes? The study confirms that the different portrayals are shown from Enola Holmes’ physical appearance, thought, and personality. Her masculine appearance was against the normative beauty standard for most women in the nineteenth-century tradition. Her critical and logical thought challenged the stereotypical gender role, which positioned women as less intelligent than men. Moreover, her independent and courageous personality highlighted the different traits of Enola Holmes as a young woman at that time. The characterizations reflect liberal feminism by emphasizing women’s autonomy and gender equality between men and women.